(untitled) (Práxis Educativa, 2019)
In this article, we present reflections on the Arrangements of Education Development (ADEs, the acronym in Portuguese) elaborated in the search for new forms of coordination and cooperation among the federal entities for the construction of a National Education System and for the improvement in the quality of education. The analysis points out that the ADEs are becoming an strategy in intergovernmental relations, which involves territorial associativism, horizontal collaboration, networking among municipalities with similar geographic, social and economic characteristics, and the establishment of cooperation agreements and partnerships with public, private and non-governmental institutions. The results indicate that the construction of this new model of cooperation as a space for the private sector in the State structure, whether for profit or not, has implications for the democratization of education. Keywords: Arrangements for the Development of Education. Collaborative arrangements. Public-private partnership.